2009
DOI: 10.1097/01.pra.0000351879.52883.10
|View full text |Cite
|
Sign up to set email alerts
|

Limited Evidence for the Effectiveness of P.R.N. Medications Among Psychiatric Inpatients

Abstract: The use of medications on a p.r.n. basis on psychiatric inpatient wards is common and widespread but without clear evidence of effectiveness. While individual studies have explored the use of p.r.n. medications in patients receiving scheduled psychotropic medications, no systematic review of the effectiveness of this use of p.r.n. medications has been done. A MEDLINE search was performed of all articles published in English between 1966 and November 2008. Studies were included only if they involved psychiatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Srivastava (2009) has pointed out that agitation is a vague and illdefined concept that could be seen to cover a multitude of behaviors. The most common antecedent documented was threatened or actual violence but it is likely that when PRN was used to prevent or manage serious incidents then these would be more likely to be documented in the patient's case notes than when PRN was used in less pressing circumstances or at patient request.…”
Section: Discussionmentioning
confidence: 99%
“…Srivastava (2009) has pointed out that agitation is a vague and illdefined concept that could be seen to cover a multitude of behaviors. The most common antecedent documented was threatened or actual violence but it is likely that when PRN was used to prevent or manage serious incidents then these would be more likely to be documented in the patient's case notes than when PRN was used in less pressing circumstances or at patient request.…”
Section: Discussionmentioning
confidence: 99%
“…Another problem is that there is a lack of scientific evidence for the effectiveness of PRN medication. There have been two systematic reviews of the subject and both of these failed to find good-quality evidence of the efficacy of PRN medication (Chakrabarti, Whicher, Morrison, & Douglas-Hall, 2007;Srivastava, 2009). Neither review identified any randomised controlled trials of PRN medication and Chakrabarti et al (2007) concluded that the current practice of making common use of PRN 'is based on clinical experience and habit rather than high quality evidence'.…”
Section: Introductionmentioning
confidence: 94%
“…Like Thapa and colleagues, Smith et al (2008) concluded there had been a reduction in unnecessary patient exposure to medication and that the hospitals concerned had become safer places. Patients receiving PRN medication are at increased risk of drug interactions and side effects (Davies et al, 2007;Srivastava, 2009) and those prescribed PRN antipsychotics may thereby be exposed to high-dose antipsychotics and antipsychotic polypharmacy with the associated increase in physical morbidity such as QTc prolongation, extra-pyramidal side effects, sedation, etc. (Milton, Lawton, Smith, & Buckley, 1998;Paton, Barnes, Rose-Cavanagh, Taylor, & Lelliott, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…). The most frequently prescribed PRN medications are hypnotics, anxiolytics, and antipsychotics (Mullen & Drinkwater ; Srivastava ; Wright et al . ).…”
Section: Introductionmentioning
confidence: 99%